Analysis of Electromagnetic Environment around High-speed Railway Platform - SONG Chaowei; LIU Mingguang; WANG Xu; TIAN Hao; LI Wei (机车电传动)
In order to research whether electromagnetic environment on platform of high-speed railway met the standard by International Commission on Non-Ionizing Radiation Protection (ICNIRP), distribution of power-frequency electromagnetic field was calculated and analyzed by numerical calculation. To question of the existing of "big size area and small size element" among the catenary in railway platform area, equivalent models of human body, lines, trains and platform were built and electric field intensity and magnetic flux density of the platform area were calculated by ANSYS. The result showed that power-frequency electromagnetic field was closely to the horizontal distance between monitoring point and the point where catenary wires project; The trains shield the electric field obviously and the shielding effect of chest and head on safety line were 90.9% and 74.5% respectively; But the effect of magnetic field shielded by trains was inconspicuous; Electric field intensity of the head on the white line was maximum value of 4 678 V/m when there was no train, which approached to but not outnumber the limits set of 5 kV/m by ICNIRP guideline.